Budaya Organisasi dan Perilaku Bullying Sesama Rekan Kerja Perawat di RSUD I. A Moeis Samarinda: A Study Komparatif - Rusdi Rusdi; Sari Basongan (ITKES Wiyata Husada Samarinda, 2018)
Bullying behavior that has been experienced and reported, namely: acts of reviling, being bullied related to the work done and discussed about the ugliness or spreading rumors about the nurse himself. In addition, nurses who experience bullying behavior also experience decreased performance. Aims to find out the relationship between organizational culture and bullying behavior among fellow coworkers in RSUD I. A Moeis Samarinda. This type of research is descriptive analytic with Cross Sectional approach. The population of this study, all nurses working at I.A Moeis Hospital in Samarinda were 164 people with a sample of 62 nurses. The study uses probability sampling techniques with simple random sampling and uses the chi square test. Research conducted by researchers showed that from 62 respondents, the statistical test results obtained p value 0.643 while the trophy α = 0.05, it can be seen that the value of p Value> α (0.643> 0.05), which indicates that Ha is rejected Ho accepted but not significant. There is no significant relationship between organizational culture and bullying behavior among fellow nurse colleagues in RSUD I. A Moeis Samarinda.